2016
DOI: 10.1002/jor.23359
|View full text |Cite
|
Sign up to set email alerts
|

Fractures of the tibial plateau involve similar energies as the tibial pilon but greater articular surface involvement

Abstract: Patients with tibial pilon fractures have a higher incidence of post-traumatic osteoarthritis than those with fractures of the tibial plateau. This may indicate that pilon fractures present a greater mechanical insult to the joint than do plateau fractures. We tested the hypothesis that fracture energy and articular fracture edge length, two independent indicators of severity, are higher in pilon than plateau fractures. We also evaluated if clinical fracture classification systems accurately reflect severity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Our definition of high‐energy may have impacted the finding that we were unable to detect a difference in the inflammatory marker concentration between high‐energy and low‐energy injuries. Some researchers have begun to quantify fracture energy through CT scans and this may be a more objective method of comparing energy of injury . Also, while we only included patients who were less than 24 h from injury, inflammatory cytokines concentrations can change within a matter of hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our definition of high‐energy may have impacted the finding that we were unable to detect a difference in the inflammatory marker concentration between high‐energy and low‐energy injuries. Some researchers have begun to quantify fracture energy through CT scans and this may be a more objective method of comparing energy of injury . Also, while we only included patients who were less than 24 h from injury, inflammatory cytokines concentrations can change within a matter of hours.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have begun to quantify fracture energy through CT scans and this may be a more objective method of comparing energy of injury. 23,24 Also, while we only included patients who were less than 24 h from injury, inflammatory cytokines concentrations can change within a matter of hours. In this study, the timedependent concentration alterations may be limited by CYTOKINES PLAFOND AND PLATEAU FRACTURES our narrow inclusion criteria and by the fact that our biomarker measurements were done on joint fluid from a relatively closed compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Fracture classification systems are often used to provide a clinician-assessed indicator of fracture severity but suffer from poor inter-observer reliability when clinicians' place fracture patterns into categorical classification schemes. 3,4 This study demonstrated poor inter-observer reliability in classifying DICAFs by the Sanders Classification (concordance τ = 0.6, p=0.0074). The Sanders classification is commonly used to assess DIACFs and has been previously found to be prognostic of long-term patient outcomes.…”
Section: Correlation Of Fracture Energy With Sanders Classificationmentioning
confidence: 70%
“…The energy range for DIACFs was found to be 14.14-26.87 J. Dibbern, et al used a similar methodology and reported fracture energies for tibial plateau fractures (3.2-33.2 J) and for pilon fractures (3.6-32.2 J). 3 Thomas et al reported pilon fracture energy range from 5.2-27.2 J. 1 Compared to plateau and pilon fractures, the energy range for calcaneus fractures appears to be narrower and focused on the upper end of the spectrum, suggesting it may take consistently more energy to break the calcaneus.…”
Section: Correlation Of Fracture Energy With Sanders Classificationmentioning
confidence: 99%
See 1 more Smart Citation